2020
DOI: 10.1007/s00167-020-06203-1
|View full text |Cite
|
Sign up to set email alerts
|

Trends of anterior cruciate ligament reconstruction in children and young adolescents in Italy show a constant increase in the last 15 years

Abstract: Purpose The aim of this 15-year nationwide study was to investigate the trend in ACL reconstructive surgeries in patients younger than 15 years old in Italy, as well as their social and economic impact. Materials and methodsThe National Hospital Discharge records (SDO) collected by the Italian Ministry of Health in the 15-year period between 2001 and 2015 were analyzed. This contains anonymous data including patients' age, gender, ICD-9-CM codes for diagnosis and intervention, census region, region of hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
0
14
0
3
Order By: Relevance
“…Numerous epidemiological studies have demonstrated an increase in the incidence of anterior cruciate ligament (ACL) injuries occurring in pediatric and adolescent patients over the past 2 decades, likely as a result of increased participation in competitive sports. 6,8,29,32,35,46,47 These findings are concerning because rates of secondary ACL injuries are considerably higher than in adult populations. Another issue regarding the management of these patients is the controversy regarding whether operative versus nonoperative treatment is optimum in pediatric patients (except in those who have repairable additional injuries in whom there is agreement that early ACL reconstruction [ACLR] and meniscal repair should be performed).…”
mentioning
confidence: 99%
“…Numerous epidemiological studies have demonstrated an increase in the incidence of anterior cruciate ligament (ACL) injuries occurring in pediatric and adolescent patients over the past 2 decades, likely as a result of increased participation in competitive sports. 6,8,29,32,35,46,47 These findings are concerning because rates of secondary ACL injuries are considerably higher than in adult populations. Another issue regarding the management of these patients is the controversy regarding whether operative versus nonoperative treatment is optimum in pediatric patients (except in those who have repairable additional injuries in whom there is agreement that early ACL reconstruction [ACLR] and meniscal repair should be performed).…”
mentioning
confidence: 99%
“…So even though this study analyzes the adult population, data from those whose age was 15 years or older were included in the present study (starting from the age group 15–19 years old). The age group 0–14 years old was included in the pediatric and young adult population [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, considering this way of census and the frequency of data updating, the high information content allows the performance of important clinical-epidemiological analyses to evaluate the effectiveness of the assistance provided and potential health planning interventions [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…The annual incidence of anterior cruciate ligament (ACL) injuries among young and middle-aged athletes continues to rise, most of which are surgically reconstructed (ACL reconstruction [ACLR]) with the hopes of restoring knee stability and allowing the athlete to return to their preinjury level of sport. 1,2 Unfortunately, between 15% and 35% of ACLR patients who successfully return to sport will sustain a second ACL injury to either their surgical or contralateral limb. 3,4 Along with the risk for second ACL injuries, ACLR patients have an elevated risk for injuring other knee joint structures (e.g., meniscus), 5 developing early signs of osteoarthritis, 6 and having selfreported joint pain and impaired quality of life.…”
Section: Introductionmentioning
confidence: 99%